Extreme 5-dimensional black holes with SU(2)-symmetric horizons - Eric Bahuaud; Sharmila Gunasekaran; Hari K Kunduri; Eric Woolgar (Journal of High Energy Physics)
Abstract We show that the near horizon geometry of 5-dimensional extreme (i.e., degenerate) stationary vacuum black holes, with or without cosmological constant, whose event horizons exhibit SU(2) symmetry must be that of a Berger sphere.